Accommodation of large cargo within Golgi cisternae - Machamer, Carolyn E. (Springer Berlin Heidelberg, 2013)
In mammalian cells, the Golgi complex has an elaborate structure consisting of stacked, flattened cisternal membranes collected into a ribbon in the center of the cell. Amazingly, the flattened cisternae can rapidly dilate to accommodate large cargo as it traffics through the organelle. The mechanism by which this occurs is unknown. Exocytosis of large cargo is essential for many physiological processes, including collagen and lipoprotein secretion, and defects in the process lead to disease. In addition, enveloped viruses that bud into the endoplasmic reticulum or Golgi complex must also be transported through Golgi cisternae for secretion from the infected cell. This review summarizes our understanding of intra-Golgi transport of large cargo, and outlines current questions open for experimentation.